Pengembangan Skala Kepatutan Sosial Berdasarkan Marlowe-Crowne Social Desirability Scale (Mcsds) Versi 33 Item - Susilo Wibisono (UIN Syarif Hidayatullah Jakarta, 2019)
One way to reduction social desirability bias on quantitative research was done by using social desirability as control variable. Identification of social desirability on research's participants was assessed by using Marlowe-Crowne Social desirability Scale (MCSDS) since decade 1960. This research aims to construct equivalent items with MCSDS and analyze to prove it. Research's participants was 300 undergraduate students. The result of analysis shows that items constructed doesn't fulfill yet the criterias of equivalency. Result of factor analysis on version 1 questionnaire shows some items in attribution and denial factor doesn't have significant correlation with its loading factor, so they must be eliminated.